Castle Island: A Visit with Don Kracht - Don Kracht (Oz, 2009)
Don Kracht, a retired high school algebra teacher, has been building a castle in his Junction City, Kansas backyard since 1993. The story of Mr. Kracht’s castle begins in 1977 when he had a well dug for his garden.